miR-449a/miR-340 reprogram cell identity and metabolism in fusion-negative rhabdomyosarcoma - Enrico Pozzo; Laura Yedigaryan; Nefele Giarratana; Chao-chi Wang; Gabriel Miró Garrido; Ewoud Degreef; Vittoria Marini; Gianmarco Rinaldi; Bernard K. van der Veer; Gabriele Sassi; Guy Eelen; Mélanie Planque; et al. (Cell Reports)
Summary: Rhabdomyosarcoma (RMS), the most common pediatric soft tissue sarcoma, arises in skeletal muscle and remains in an undifferentiated state due to transcriptional and post-transcriptional regulators. Among its subtypes, fusion-negative RMS (FN-RMS) accounts for the majority of diagnoses in the pediatric population. MicroRNAs (miRNAs) are non-coding RNAs that modulate cell identity via post-transcriptional regulation of messenger RNAs (mRNAs). In this study, we identify miRNAs impacting FN-RMS cell identity, revealing miR-449a and miR-340 as major regulators of the cell cycle and p53 signaling. Through miR-eCLIP technology, we demonstrate that miR-449a and miR-340 directly target transcripts involved in glycolysis and mitochondrial pyruvate transport, inhibiting the mitochondrial pyruvate carrier (MPC) complex. Pharmacological MPC inhibition induces a similar metabolic shift, reducing metastatic potential and leading to cell cycle exit. Overall, miR-449 and miR-340 orchestrate FN-RMS cell identity, positioning MPC inhibition as a strategy to shift FN-RMS cells toward a non-tumorigenic, quiescent state.